(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2009)
Fatalities related to blast are usually caused by ignition of inflammable substance(s), that may be solid, liquid or in gaseous form. A sub category of these deaths may include death by explosive devices. Oxygen is the third most abundant element in the universe by mass after hydrogen and helium and the most abundant element by mass in the Earth’s crust. Highly concentrated sources of oxygen promote rapid combustion. Fire and explosion hazards exist when concentrated oxidants and fuels are brought into close proximity; however, an ignition event, such as heat or a spark, is needed to trigger combustion. Few cases of injury due to oxygen cylinder blast have been reported in the media reports and scientific literature. However detailed post-mortem findings and preventive strategies have not been discussed frequently. The paper is intended to focus on this aspect of such fatal eventualities.